THU0237 Inflammatory lesions of the sacroiliac joints, but not of the spine, are of high utility for axspa recognition: results of the ilos-desir study. (12th June 2018) - Moltó, A.; Gossec, L.; Lefevre-Colau, M.; Foltz, V.; Beaufort, R.; Laredo, J.; Richette, P.; Dieudé, P.; Goupille, P.; Feydy, A.; Dougados, M.
Abstract : Objectives: To evaluate the performance of MRI inflammatory lesions suggestive of axSpA for the axSpA recognition Methods: Observational cross-sectional national multicentre study. Patients : a) Recent onset axSpA patients: first, a sample of 100 patients representative in terms of imaging abnormalities of the global DESIR recent onset axSpA cohort were selected. b) Recent onset CBP patients: consecutive in- and outpatients consulting for recent (>3 months but <5 years) mechanical CBP, initiating before the age of 45 y and with a maximum age of 50 y, in four tertiary care Hospitals were included in the study. Imaging: MRI scans (T2-STIR and T1 sequences) of the SIJ and full spine were performed in both groups with identical protocol. Central reading: an experienced reader (AM) centrally read all MRI scans, blinded for clinical diagnosis. Statistical analysis: Sensitivity, specificity and positive likelihood ratio of each lesion were calculated. Results: A total of 98 patients with recent onset CBP were included, and compared to 100 recent onset axSpA patients. Age and gender were comparable (mean (SD) 36.2 (9.9) vs. 32.2 (8.7)y, and 41.8% and 45% males, in the CBP vs. axSpA groups, respectively). MRI inflammatory lesions of the SIJ were quite frequent in the CBP group (25% patients with at least one inflammatory lesion) but were significantly more frequently observed in the axSpA group (table 1), with a mean SIJ - SPARCC score of 4.9 (8.8) vs. 0.6 (1.3), p<0.001. The ASAS definition of MRI sacroiliitis presented a high specificity and a good positive likelihood ratio. Conversely, prevalence of inflammatory lesions of the spine was very frequent in the CBP group and not significantly lower compared to the axSpA group (SPARCC spine 5.6 (13.5) vs. 3.3 (5.8), NS, in the axSpA vs. CBP groups, respectively). Regardless the definition of a positive MRI for the spine applied, performances were not good Conclusions: ASAS definition of a positive MRI-sacroiliitis performed very well for axSpA recognition; however, definitions proposed for a positive MRI-spine suggestive of axSpA did not seem to perform adequately in this recent disease stage. This supports the idea of not including a positive MRI of the spine in the ASAS classification criteria. Disclosure of Interest: None declared